Analisis Morfologi Nisan Sultan-Sultan Kerajaan Samudera Pasai - Ambo Asse Ajis (Kemendikbud, 2020)
Archaeological evidence of the existence of the sultans of Samudera Pasai Kingdom is marked by the remains of gravestones that mention their name, title and year of death. From these data we can arrange the order of the sultan’s name, title, name of his parents and the year of his death. And, not only that, this archaeological evidence can also map the morphology (form) of tomb and the type of material. As for the study of the morphology of the gravestones of the sultans of Samudera Pasai Kingdom, until now no one has done it. Therefore, this paper becomes a kind of introduction for those interested in the study of the ancient tombstone of Samudera Pasai Kingdom. The method of writing this work uses a historiographic approach in examining the time sequence of the gravestones. This paper then succeeded in recording the morphology of the gravestones and the types of materials according to the tombstone sequences of the sultans of Samudera Pasai Kingdom, starting from the first sultan to the last sultan.